“Colorful Science Kit”: Pengembangan Alat Pembelajaran Berbasis Pewarna Warni untuk Meningkatkan Literasi Sains Anak PAUD - Ima Ismail; Wa Ode Rizka Fauziah Ali (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2022)
This study aims to develop and test the feasibility of the “Colorful Science Kit” as a colorful-based learning media to improve early childhood science literacy. The study used the Research and Development (R&D) method with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of 20 children aged 5–6 years at an early childhood education institution. Data collection was carried out through observation, interviews, documentation, and expert validation using a Likert scale instrument. The validation results showed that the media obtained a very feasible category with an average percentage of 91%. The implementation of the media showed an increase in children’s scientific literacy skills, especially in the skills of observing, grouping, predicting, and communicating the results of simple experiments. Children showed high enthusiasm during the color exploration activities and were able to work actively together in small groups. The use of color-based media also helped improve children’s attention, creativity, and communication skills during the learning process. The results of the study showed that the “Colorful Science Kit” was effectively used as an interactive and fun science learning media in early childhood education. This media is recommended as a contextual learning innovation to support the development of scientific literacy in early childhood education (PAUD).